Antibakteri Deodorant Spray Minyak Atsiri Bunga Cengkeh terhadap Staphylococcus aureus - Dhifa Wira Wicaksana; Edy Suwandi; Etiek Nurhayati; Sugito Sugito; Imma Fatayati; Emilda Sari (poltekkes kemenkes pontianak, 2026)
Body odor is a common problem that can affect personal comfort and social confidence. Understanding the relationship between clove flower essential oil concentration and the inhibition of Staphylococcus aureus growth is important for improving the effectiveness of natural deodorant formulations. This study aimed to analyze the relationship between the concentration of clove flower essential oil deodorant spray and the inhibition of Staphylococcus aureus among samples tested at the laboratory. This study used an experimental design with a total sample of 30 samples. Data were collected using the bacterial culture diffusion method on Mueller Hinton Agar (MHA) media and analyzed using the simple linear regression test with a significance level of p < 0.05. The results showed that 15% of samples demonstrated antibacterial activity. Statistical analysis revealed a significant relationship between clove flower essential oil deodorant spray concentration and inhibition of Staphylococcus aureus growth (p = 0.000). The concentration of clove flower essential oil deodorant spray significantly influences the inhibition of Staphylococcus aureus. Early development and utilization of natural-based deodorant formulations are recommended to improve product effectiveness and safety.